Implementasi Kebijakan Tentang Kawasan Tanpa Rokok di Kabupaten Bandung - Indra Aditya Prayoga (Jurnal Indonesia Sosial Sains, 2022)
Implementation of the Policy on No Smoking Areas in Bandung Regency with a Study of the Bandung Regency Regional Government Office Complex in this study was conducted to determine the implementation of the policy by exploring various primary and secondary sources of information using a descriptive qualitative approach that describes a certain situation of the facts that occur in the research process, both in the form of behavior, perception, motivation, action and others without manipulating the observed phenomena. The dimensions that become a measuring tool for implementation are: Content of Policy and Context of Policy. The results showed that the Implementation of the Policy on Smokefree Areas in Bandung Regency with a Study of the Bandung Regency Regional Government Office Complex carried out by the Bandung Regency KTR Task Force was not quite optimal. Actually, in terms of the content of the policy itself, it is quite complete and detailed, which includes all the rules that limit negative smoking activities, especially in areas that have been determined in the policy content. It's just that in terms of the policy environment there are still weaknesses that make this policy not well implemented, such as still not taking firm action and imposing administrative sanctions, especially legal sanctions on policy violators.